Headpiece Domain of Dematin Regulates Calcium Mobilization and Signaling in Platelets - Wieschhaus, Adam J. (American Society for Biochemistry and Molecular Biology, 2012)
Dematin is a broadly expressed membrane cytoskeletal protein that has been well characterized in erythrocytes and to a lesser extent in non-erythroid cells. However, dematin's function in platelets is not known. Here, we show that dematin is abundantly expressed in both human and mouse platelets. Platelets harvested from the dematin headpiece knock-out (HPKO) mouse model exhibit a striking defect in the mobilization of calcium in response to multiple agonists of platelet activation. The reduced calcium mobilization in HPKO platelets is associated with concomitant inhibition of platelet aggregation and granule secretion. Integrin α(IIb)β(3) activation in response to agonists is attenuated in the HPKO platelets. The mutant platelets show nearly normal spreading on fibrinogen and an unaltered basal cAMP level; however, the clot retraction was compromised in the mutant mice. Immunofluorescence analysis indicated that dematin is present both at the dense tubular system and plasma membrane fractions of platelets. Proteomic analysis of dematin-associated proteins in human platelets identified inositol 1,4,5-trisphosphate 3-kinase isoform B (IP3KB) as a binding partner, which was confirmed by immunoprecipitation analysis. IP3KB, a dense tubular system protein, is a major regulator of calcium homeostasis. Loss of the dematin headpiece resulted in a decrease of IP3KB at the membrane and increased levels of IP3KB in the cytosol. Collectively, these findings unveil dematin as a novel regulator of internal calcium mobilization in platelets affecting multiple signaling and cytoskeletal functions. Implications of a conserved role of dematin in the regulation of calcium homeostasis in other cell types will be discussed.